Material assisted laser ablation - CHAE JUNGHUN; JAIN KANTI (2013)
This invention provides photoablation-based processing techniques and materials strategies for making, assembling and integrating patterns of materials for the fabrication of electronic, optical and opto-electronic devices. Processing techniques of the present invention enable high resolution and/or large area patterning and integration of porous and/or nano- or micro-structured materials comprising active or passive components of a range of electronic devices, including integrated circuits (IC), microelectronic and macroelectronic systems, microfluidic devices, biomedical devices, sensing devices and device arrays, and nano- and microelectromechanical systems.